1994
DOI: 10.1021/j100089a010
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Population Relaxation of Perylene in n-Alkanes. The Role of Solvent Local Structure in Long-Range Vibrational Energy Transfer

Abstract: We have measured the vibrational population relaxation times of the Raman active v7 mode (1375 cm-') and(v7 + v15) combination mode (1733 cm-') of perylene in eight liquid n-alkanes using ultrafast stimulated emission spectroscopy. The vibrational population relaxation time of the perylene v7 mode ranges from -300 to < l o ps depending on the n-alkane solvent chain length, but there is no simple correspondence between alkane length and TI for v7. Energy transfer from the perylene v7 vibrational mode to a speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
76
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(80 citation statements)
references
References 6 publications
4
76
0
Order By: Relevance
“…More recently, Blanchard et al have measured the fluorescence dynamics of Pe in n-alkanes of different length using stimulated emission spectroscopy with 10 ps resolution. 28 The rise time of the fluorescence in a wavelength region corresponding to S 1 (V ) 0) f S 0 (V * 0) emission was attributed to the lifetime of the vibrational excited state. Time constants ranging from less than 10 to about 400 ps were reported, but no relationship between alkane length and VER time constant was found.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Blanchard et al have measured the fluorescence dynamics of Pe in n-alkanes of different length using stimulated emission spectroscopy with 10 ps resolution. 28 The rise time of the fluorescence in a wavelength region corresponding to S 1 (V ) 0) f S 0 (V * 0) emission was attributed to the lifetime of the vibrational excited state. Time constants ranging from less than 10 to about 400 ps were reported, but no relationship between alkane length and VER time constant was found.…”
Section: Introductionmentioning
confidence: 99%
“…Many experimental and theoretical studies have been reported on VER in the last decade [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. that IVR is further classified into two processes in solutions; the fast IVR that takes place in tens of femtoseconds to sub picoseconds time scales and the slow IVR in a few picoseconds time scale [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Blanchard et al studied VER of S 0 perylene and S 0 1-methylperylene in various solvents by using picosecond stimulated emission spectroscopy [9][10][11]. They investigated VET taking place in time scales slower than tens of picoseconds.…”
Section: Introductionmentioning
confidence: 99%
“…The dielectric friction can be modeled using continuum theories of NeeZwanzig (NZ) (Nee and Zwanzig, 1970), which treats the solute as a point dipole rotating in a spherical cavity, Alavi-Waldeck (AW) (Alavi and Waldeck, 1991b;1993) model which is an extension of the NZ theory where the solute is treated as a distribution of charges instead of point dipole and the semiempirical approach of van der Zwan and Hynes (vdZH) (van der Zwan and Hynes, 1985) in which fluorescence Stokes shift of the solute in a given solvent is related to dielectric friction. Conversely, the results of neutral and nonpolar solutes deviate significantly from the hydrodynamic predictions at higher viscosities (Waldeck et al, 1982;Canonica et al, 1985;Phillips et al, 1985;Courtney et al, 1986;Ben Amotz and Drake, 1988;Roy and Doraiswamy, 1993;Williams et al, 1994;Jiang and Blanchard, 1994;Anderton and Kauffman, 1994;Brocklehurst and Young, 1995;Benzler and Luther, 1997;Dutt et al, 1999;Ito et al, 2000;Inamdar et al, 2006). These probes rotate much faster than predicted by the SED theory with stick boundary condition and are described by either slip boundary condition or by quasihydrodynamic theories.…”
Section: Introduction To Rotational Dynamicsmentioning
confidence: 93%
“…In the two limiting cases of hydrodynamic stick and slip for a nonspherical molecule, the value of C follows the inequality, 0< C ≤ 1 and the exact value of C is determined by the axial ratio of the probe. It is observed that the experimentally measured rotational reorientation times of number of the nonpolar solutes (Waldeck et al, 1982;Canonica et al, 1985;Phillips et al, 1985;Courtney et al, 1986;Ben Amotz and Drake, 1988;Roy and Doraiswamy, 1993;Williams et al, 1994;Jiang and Blanchard, 1994;Anderton and Kauffman, 1994;Brocklehurst and Young, 1995;Benzler and Luther, 1997;Dutt et al, 1999;Ito et al, 2000;Inamdar et al, 2006) could be described by the SED theory with slip boundary condition (subslip behavior). For a homologous series of solvents such as alcohols or alkanes, the normalized reorientation times decreased as the size of the solvent is increased.…”
Section: Hydrodynamic Theorymentioning
confidence: 99%